Composite Layer Formation with Island Nanostructures in Vacuum - S. V. Sidorova; I. E. Pimenov; A. D. Kouptsov; A. A. Felde (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. The current trends in the development of electronics require miniaturized devices with increased performance at affordable costs. The introduction of nanoscale structures and layers based thereon, including island structures, offers great opportunities for the development of various branches of electronics. Island thin films and nanostructures (INS) are thin-film structures whose formation has been completed at the initial stages. The size of the islands does not exceed 100 nm in the lateral and vertical directions, which makes the INS arrays to exhibit dimensional effects (electrical, magnetic, optical, mechanical, etc.). The formation of a composite dielectric layer with embedded conductive INS presents particular interest.Aim. Development of a technique and testing of formation modes of a composite coating with INS.Materials and methods. The research was carried out at the Department of Electronic Technologies in Mechanical Engineering of Bauman Moscow State Technical University. The research materials alumina and copper. A MVTU-11-1MC vacuum unit, equipped with magnetron and ion sources, was used as technological equipment. The roughness of the substrate and coating surfaces was studied using a Solver NEXT atomic force microscope; the geometric parameters of the composite layer were studied using a CROSSBEAM 550 scanning electron microscope.Results. The average absolute deposition rates for copper and alumina were 25.9 and 0.3 nm/min, respectively. A conductive insert with a diameter of 25 mm and a width of 0.46 mm was used to form a composite structure with a diameter of 100 nm and a distance between the islands of 3…5 nm. To obtain a homogeneous structure and a high-quality adhesion of the composite layer to the substrate, preliminary ion treatment of the substrate for 120 s was required.Conclusion. The developed method for forming a composite coating with INS involves the use of a combined target. The results obtained can be used when creating composite thin-film coatings from dielectric and conductive nanoscale structures by magnetron sputtering in vacuum.